Adakah Reka Bentuk Emoji Senyum Dengan Pelbagai Tahap Realistik Pada Poster Bercetak Memberi Kesan Yang Signifikan Dalam Menstimulasi Kesedaran Pengguna? - Daud, Norlida; Mohamad Ali, Ahmad Zamzuri (Idealogy Journal; Vol 6 No 2 (2021): Idealogy Journal (September 2021), 2021)
This research was aimed to study the effects of smiley emoji in printed poster with flat and skeuomorphism design approach in stimulating user’s awareness. Six safety awareness posters with six different smiley emoji designs have been developed and tested, i.e. line emoji, coloured line emoji, vector emoji, line and shadow emoji, three-dimensional (3D) emoji and realistic emoji. The quasi-experimental design was applied in answering the research question derived and the data obtained was analysed using one-way ANOVA and post hoc test. 700 first year engineering students from Universiti Teknologi Mara (UiTM) were involved as the research sample. Each awareness poster was evaluated by 100 students including a text only poster, i.e. without emoji, as the control group. User Experience Questionnaire (UEQ), specifically stimulation scale, was utilised in obtaining feedback from respondents. In conclusion, this study indicated that the use of smiley emoji in an awareness poster was more effective than poster with text alone. However, the design aspects of the smiley emoji are found to have an impact on users. Therefore, this study recommends coloured line emoji, vector emoji, line and shadow emoji and 3D emoji to be the better design choice for awareness poster in printed form. Keywords Emoji, flat, poster, stimulation, skeuomorphism